The light color quality of LED operating at winter temperatures - Tabaka, Przemysław; Rozga, Pawel (Photonics Letters of Poland, 2019)
The paper presents the results of calculations of colorimetric parameters of LED sources operating at a temperature range from -25oC to 25oC. The chromaticity coordinates and color rendition quality parameters were calculated on the basis of registered spectral distributions of radiation. For individual LED chromaticity shift is illustrated at CIE 1931 x,y diagram with 3 step and 7 step MacAdam ellipses. Full Text: PDF References J. P. Freyssinier, D. Frering, J. Taylor, N. Narendran, and P. Rizzo, Reducing lighting energy use in retail display windows. Sixth International Conference on Solid State Lighting, Proceedings of SPIE 6337, 63371L (2006). CrossRef Aman, M. M., et al., 2013. Analysis of the performance of domestic lighting lamps, Energy Policy, CrossRef E. Elijošiute, J. Balciukevičiute, G. Denafas, Life cycle assessment of; compact fluorescent and incandescent lamps: Comparative analysis. Environ Res. Eng. Manag. 61 (3), pp. 65-72, (2012), CrossRef D. Czyzewski, LED substitutes of conventional incandescent lamps Przeglad Elektrotechniczny R. 88, No. 11 (2012), CrossRef P. Tabaka, P. Rozga, Assessment of methods of marking LED sources with the power of equivalent light bulb, ulletin of the Polish Academy of Sciences. Technical Sciences, Vol. 65, No. 6, (2017) CrossRef I. Fryc, P. Jakubowski, K. Kołacz, Analysis of optical radiation parameters of compact discharge HID lamps and LED COB modules used for illuminating shop windows, Przeglad Elektrotechniczny,R. 93, No 11, (2017); pp. 186-189, CrossRef T. Kawabata, Y. Ohno; Optical measurements of OLED panels for lighting applications, pp 1176-1186 Jun 2013, Journal of Modern Optics, Vol. 60, 2013 Issue 14 CrossRef W. Żagan, Conditions necessary to replacing the conventional lamps by energy-saving lamps, Przeglad Elektrotechniczny R. 85, No. 5, pp. 100-104, (2009). DirectLink P. Tabaka; Influence of Ambient Temperature on Colour Properties of Low-Pressure Fluorescent Lamps, Light & Engineering, Vol. 23; No. 2; (2015). DirectLink W. R. Ryckaert, et al., Linear LED tubes versus fluorescent lamps: An evaluation. Energy Build. 49, pp. 429-436. CrossRef M. Zalesinska, J. Zablocka, K. Wandachowicz, Evaluation of Selected Parameters of Non-Directional Household Lamps, Conference: 2018 VII. Lighting Conference of the Visegrad Countries (Lumen V4), CrossRef I. Fryc; Measurement techniques of optical LEDs properties performed with compliance conformity with CIE 127:2007 standard, Przeglad Elektrotechniczny R. 85, No. 11, pp. 317-319, (2009) DirectLink IESNA, IES Approved Method: Measuring Lumen Maintenance of LED Light Sources. IES LM-80-08', IES Subcommittee on Solid-State Lighting of the IES Testing Procedures Committee (2018). DirectLink D. B. Judd, Estimation of chromaticity differences and nearest color temperature on the standard 1931 ICI colorimetric coordinate system. J. Opt. Soc. America 26 (11), 421, (1936) CrossRef CIE 177:2007 Colour Rendering of White LED Light Sources DirectLink CIE 13.3-1995 Method of Measuring and Specifying Colour. DirectLink CIE 224:2017 Colour Fidelity Index for accurate scientific use DirectLink CIE 15:2004 Colorimetry. DirectLink D. Mozysrska, M. Wyrwas, I. Fryc, The determination of the LEDs colorimetric parameters, in the range of their operating temperature, Przeglad Elektrotechniczny, R. 93, No. 4a, pp. 232-234, (2012). DirectLink J. Kowalska, Analysis of parameters describing the quality of the color rendering of light sources according to the IES TM-30-15 and the CIE 013.3-1995, Przeglad Elektrotechniczny, R. 93, No. 6; pp. 50-54, (2017) CrossRef J. Kowalska, I. Fryc, Colour rendition quality of typical fluorescent lamps determined by CIE Colour Fidelity Index and Colour Rendering Index, Przeglad Elektrotechniczny, R. 95, No. 7; (2019), pp. 94-97 CrossRef J. Kowalska, Ambiguity and limitations in determining the quality of the color rendering of light sources by index Ra (CIE CRI), Przeglad Elektrotechniczny, R. 93 No. 5, pp. 74-78, (2017) CrossRef I. Fryc, J. Fryc, A. Wasowski, Considerations about determining color rendering of light sources, Przeglad Elektrotechniczny, R. 92 No. 2, pp. 218-223, (2016) CrossRef I. Fryc, LED's spectral power distribution under different condition of operating temperature and driving current, Przeglad Elektrotechniczny, R. 86, No. 10, pp. 187-189, (2010). DirectLink A. David, P. Fini, K. Houser et al., Development of the IES method for evaluating the color rendition of light sources, Optics Express; Vol. 23; Issue 12, pp. 15888-15906, (2015). CrossRef K. Houser, M. Mossman, K. Smet et al, Tutorial, Color Rendering and Its Applications in Lighting, LEUKOS; Vol. 12, Issue 1-2; pp. 7-26; (2016). CrossRef